Proceedings of the 2003 International Symposium on Low Power Electronics and Design - ISLPED '03 2003
DOI: 10.1145/871506.871538
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and scaling trends of leakage control techniques for sub-130nm CMOS technologies

Abstract: This paper compares the effectiveness of different leakage control techniques in deep submicron (DSM) bulk CMOS technologies. Simulations show that the 3-5x increase in I OFF /µm per generation is offsetting the savings in switching energy obtained from technology scaling. We compare both the transistor I OFF reduction and I ON degradation due to each technique for the 130nm-70nm technologies. Our results indicate that the effectiveness of leakage control techniques and the associated energy vs. delay tradeoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The reduction in the transistor OFF-state current due to supply scaling can be expressed as [12]: Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page. To copy otherwise, or republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee.…”
Section: Supply Scaling and Transistor Currentsmentioning
confidence: 99%
“…The reduction in the transistor OFF-state current due to supply scaling can be expressed as [12]: Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted without fee provided that copies are not made or distributed for profit or commercial advantage and that copies bear this notice and the full citation on the first page. To copy otherwise, or republish, to post on servers or to redistribute to lists, requires prior specific permission and/or a fee.…”
Section: Supply Scaling and Transistor Currentsmentioning
confidence: 99%
“…To reduce the leakage power, other circuit techniques can be used such as MTCMOS, DTCMOS, Reverse Body Bias and larger than Vdd Forward Body Bias [15,16,17,18]. Borkar et al [11] have evaluated some of these techniques and have shown that the stack effect is the most effective means to reduce leakage power, but because it lowers the active current in the normal mode operation, it is also the slowest. They have also shown that lowering voltage is inferior in terms of both leakage savings as well as in speed (low voltage underrates Ion significantly).…”
Section: Related Workmentioning
confidence: 99%
“…However, the usage of RBB requires the generation and routing of extra power supply to the body and well terminals of n-and p-MOS transistors. In addition, it requires the usage of a triple-well bulk CMOS process [11] increasing the overall implementation cost. MTCMOS is in effect a dynamic implementation of the RBB scheme, which makes it more costly in terms of fabrication.…”
Section: Related Workmentioning
confidence: 99%
“…This percentage is expected to increase with technology scaling. Simulation results in [7] predict that the transistor off-state current per micron of transistor width increases by a factor of 3-5 per generation. As will be shown in Section 4, for a given package, the die temperature can be modeled as a linear function of the total power dissipation of the circuit.…”
Section: Introductionmentioning
confidence: 99%